Reactive oxygen species-related genes participate in resistance to cucumber green mottle mosaic virus infection regulated by boron in Nicotiana benthamiana and watermelon - Guo, Huiyan; Bi, Xinyue; Wang, Zhiping; Jiang, Dong; Cai, Ming; An, Mengnan; Xia, Zihao; Wu, Yuanhua (Frontiers in Plant Science, 2022)
Cucumber green mottled mosaic virus (CGMMV) infection causes acidification and rot of watermelon flesh, resulting in serious economic losses. It is widely reported the interaction relationship between boron and reactive oxygen species (ROS) in regulating normal growth and disease resistance in plants. Our previous results demonstrated that exogenous boron could improve watermelon resistance to CGMMV infection. However, the roles of ROS-related genes regulated by boron in resistance to CGMMV infection are unclear. Here, we demonstrated that CGMMV symptoms were alleviated, and viral accumulations were decreased by boron application in Nicotiana benthamiana, indicating that boron contributed to inhibiting CGMMV infection. Meanwhile, we found that a number of differentially expressed genes (DEGs) associated with inositol biosynthesis, ethylene synthesis, Ca2+ signaling transduction and ROS scavenging system were upregulated, while many DEGs involved in ABA catabolism, GA signal transduction and ascorbic acid metabolism were down-regulated by boron application under CGMMV infection. Additionally, we individually silenced nine ROS-related genes to explore their anti-CGMMV roles using a tobacco rattle virus (TRV) vector. The results showed that NbCat1, NbGME1, NbGGP and NbPrx Q were required for CGMMV infection, while NbGST and NbIPS played roles in resistance to CGMMV infection. The similar results were obtained in watermelon by silencing of ClCat, ClPrx or ClGST expression using a pV190 vector. This study proposed a new strategy for improving plant resistance to CGMMV infection by boron-regulated ROS pathway and provided several target genes for watermelon disease resistance breeding.